Form 4 biology students' drawings and misconceptions of the human digestive system - Phang, Loren (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This research is a case study aimed to investigate Form Four Biology students' drawing and misconceptions about human digestive system by using drawing, explanation and questionnaire in Kuching District, Malaysia. Ten students are selected from two secondary schools in Kuching district with purposive sampling. The instrument used in this study is self-developed by researcher based on the textbook of Form Two Science.